Conjugate forced convective heat transfer in a sandwich panel with a Kagome truss core: The effects of strut length and diameter. (25th February 2020) - Kemerli, Ubade; Kahveci, Kamil
Highlights: Complex secondary flow structures develop in the flow field. The pressure drop is highly dependent on the geometry of unit cells. Kagome core with a shorter strut length and larger strut diameter has a better heat transfer rate. KCell and Nu are quadratically dependent on the ratio of strut diameter to strut length. Abstract: Heat exchangers with a cellular metal core have become an alternative to those with louvered fins due to their high heat transfer performance and mechanical strength. Because of the multi-functionality, they are mostly used in systems such as rockets and space vehicles or in others in need of both high heat transfer performance and mechanical strength. The geometrical parameters of the unit cell of cellular metals have important effects on both fluid and heat transfer characteristics and these effects need to be studied. Accordingly, conjugate forced convective heat transfer in a sandwich panel with a Kagome truss core both with a constant heat flux (CHF) and a constant temperature (CT) boundary condition was studied numerically in this study for various values of the Reynolds number, strut length, and strut diameter. The 3D turbulent flow and heat transfer was modeled by the RNG k-epsilon turbulence model. The near-wall behavior of the flow was modelled by enhanced wall treatment. The channel was extended before and after the Kagome core to avoid entrance and exit effects. The computational results were obtained for the Reynolds numbers in the range of about 6000–17000, for the strut lengths of 3, 5 and 7 mm, and for the strut diameters of 1.3 and 1.6 mm. A nonlinear regression analysis was also performed for the pressure loss coefficient and average Nusselt number. The numerical results show that complex flow structures develop in the flow field due to the presence of unit cells. The results also show that the pressure drop along the Kagome core increases considerably with decreasing strut length and increasing strut diameter. The average Nusselt number increases significantly when the strut length is decreased and shows a small increase with an increase in the strut diameter. The effect of strut diameter on average Nusselt number becomes marginal for strut length of 3 mm. The average heat transfer rate for a fixed pumping power shows a considerable increase with a decrease in the strut length and a small increase with the strut diameter for high values of strut length. On the other hand, for the strut length of 3 mm, it shows a small decrease with an increase in the strut diameter for the CT case and remains almost constant for the CHF case.